2013
DOI: 10.1371/journal.pone.0061445
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Newt Lens Regeneration Reveals Distinct Gradients in Gene Expression Patterns

Abstract: Regeneration of the lens in newts is quite a unique process. The lens is removed in its entirety and regeneration ensues from the pigment epithelial cells of the dorsal iris via transdifferentiation. The same type of cells from the ventral iris are not capable of regenerating a lens. It is, thus, expected that differences between dorsal and ventral iris during the process of regeneration might provide important clues pertaining to the mechanism of regeneration. In this paper, we employed next generation RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 148 publications
(144 reference statements)
1
38
0
Order By: Relevance
“…The genes that were expressed differently between young and old axolotl larvae reveal age‐related differences in transcription, metabolism, cell proliferation, differentiation, and immune response. We report further insights by comparing genes identified between young and old axolotl iris to genes that were identified recently from dorsal and ventral irises of newts (Sousounis et al ).…”
Section: Introductionmentioning
confidence: 68%
“…The genes that were expressed differently between young and old axolotl larvae reveal age‐related differences in transcription, metabolism, cell proliferation, differentiation, and immune response. We report further insights by comparing genes identified between young and old axolotl iris to genes that were identified recently from dorsal and ventral irises of newts (Sousounis et al ).…”
Section: Introductionmentioning
confidence: 68%
“…These efforts have generated large expression datasets for normal and defective lens development (Agrawal et al, 2015; Anand et al, 2015; Audette et al, 2016; Chauhan et al, 2002a, 2002b; Chauss et al, 2014; De Maria and Bassnett, 2015; Greiling et al, 2009; Hawse et al, 2005, 2004, 2003; Hoang et al, 2014; Ivanov et al, 2005; Khan et al, 2016, 2015; Kumar et al, 2015; Lachke et al, 2012b, 2011; Manthey et al, 2014a; Sousounis et al, 2015, 2013; Sousounis and Tsonis, 2012; Wistow et al, 2002; Wolf et al, 2013b; Wride et al, 2003; Xiao et al, 2006). Although highly informative, early microarray studies used platforms representing only a subset of genes ( n =9,700) in the mouse genome (Chauhan et al, 2002a, 2002b).…”
Section: Genome-level Expression Profiling Of Lens Developmentmentioning
confidence: 99%
“…Besides these efforts, high-throughput expression profiling was performed on lenses in other animal models (Chauss et al, 2014; Sousounis et al, 2015, 2013). However, the strength of high-throughput expression profiling – providing genome-wide data – perhaps poses its greatest challenge, because these approaches identify thousands of transcripts that are scored as “expressed”.…”
Section: Future Of Lens Research: Toward Lens Systems Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas a typical NGS approach in eukaryote model organisms (and also niche models, e.g. [47]) reports a couple of ten thousands of transcripts in a quantitative manner, a proteomics approach allows the identification and quantification of a couple of thousand proteins in well-established model organisms. For instance, a recent study with zebrafish revealed 2,100 proteins [48], a new protocol to identify human proteins out of paraffin-embedded samples even allowed the identification of 10,000 proteins [49] (details see Box 1).…”
Section: Investigation Of Unknown Proteinsmentioning
confidence: 99%